Answer:
![g(x)=4(3)^{x+1}+8](https://tex.z-dn.net/?f=g%28x%29%3D4%283%29%5E%7Bx%2B1%7D%2B8)
Step-by-step explanation:
Given:
The original function is given as:
![f(x)=2(3)^{x+1}+4](https://tex.z-dn.net/?f=f%28x%29%3D2%283%29%5E%7Bx%2B1%7D%2B4)
The above function is stretched vertically by a factor of 2 to form the graph of
.
According to the rule of function transformations, when the graph of a function is stretched in the vertical direction by a factor of 'C', where, 'C' is a number greater than 1, then the function rule is given as:
![f(x)\to Cf(x)](https://tex.z-dn.net/?f=f%28x%29%5Cto%20Cf%28x%29)
Therefore, the function is multiplied by a factor of 'C' to get the equation of the stretched function.
Here, the the value of 'C' is 2. So, the equation of
is given as:
![g(x)=2f(x)\\g(x)=2[2(3)^{x+1}+4]\\g(x)=4(3)^{x+1}+8](https://tex.z-dn.net/?f=g%28x%29%3D2f%28x%29%5C%5Cg%28x%29%3D2%5B2%283%29%5E%7Bx%2B1%7D%2B4%5D%5C%5Cg%28x%29%3D4%283%29%5E%7Bx%2B1%7D%2B8)
Therefore, the equation of
is
.
22,000 x 2= 44,000
120%
So I think it would equal to 345,600,0
I am not sure
P.S. I am not good at math sorry if it is wrong...
9514 1404 393
Answer:
f(g(x)) = -3x^2 -2x -3
Step-by-step explanation:
<u>Given</u>:
f(x) = -x-7
g(x) = 3x^2 +2x -4
<u>Find</u>:
f(g(x))
<u>Solution</u>:
Substitute per the function definitions.
f(g(x)) = f(3x^2 +2x -4) = -(3x^2 +2x -4) -7
f(g(x)) = -3x^2 -2x -3
Answer:
i think its obtuse scalene ??
Step-by-step explanation:
i might not be right but im pretty sure
Answer:
9.4m is the answer.
Step-by-step explanation:
a = 8m
b = 5m
c = ?
According to the Pythagoras theorem,
a² + b² = c²
8² + 5² = c²
64 + 25 = c²
89 = c²
c = 9.433
Rounding off,
c = 9.4m